A rapid stain for the diagnosis of granuloma inguinale. Issue 3 (June 1990) - O'Farrell, N; Hoosen, A A; Coetzee, K; van den Ende, J
Abstract : Tissue smears were prepared from 55 men and eight women with genital ulceration using two staining techniques and examined by direct microscopy for the presence of Donovan bodies. Twenty three smears were positive using the May-Grunwald-Giemsa staining method and 23 were positive using a rapid technique, the RapiDiff stain. The RapiDiff technique is suitable for use in the diagnosis of granuloma inguinale (donovanosis) in busy sexually transmitted diseases clinics in the developing world.